치과의료기관종사자의 방사선안전관리에 대한 지식 및 태도 조사 - 한옥성; Ok Sung Han; 우승희; Seung Hee Woo; 김서연; Seo Yeon Kim (Han'guk Ch'iwisaeng Hakhoe chi, 2014)
Objectives: The aim of the study was to investigate the knowledge and attitude toward radiation safety management in dental clinic worker. Methods: A self-reported questionnaire was filled out by 294 dental clinic workers in dental hospitals and clinics in Gwangju and Jeonnam from February 17 to March 30, 2014. The questionnaire consisted of general characteristics of radiation safety(8 questions), knowledge of radiation safety(15 questions), and attitudes of radiation safety(16 questions). The survey was done by Likert 5 scale method. Results: In completion of the radiodontia courses, 84.0% of the learners were female workers. 88.0% of the learners took the theoretical and practical courses. Those who work in the university dental hospital accounted for 87.1% and those in dental clinics accounted for 83.2%. Majority of the workers took on Leaden protective clothing in order to protect the thyroid gland. Male workers had more knowledge toward the radiation safety management than the female workers. The attitude toward the radiation safety management revealed the significant differences between age, gender, academic careers, license, clinical careers and the mean number of patients per day(p<0.05). Conclusions: The radiation safety management is very important in dental clinical workers and it is necessary to enhance the attitude toward the radiation safety through continuous education.